The second order phase transition in Sn2P2S6 crystals: anharmonic oscillator model - Yu.M. Vysochanskii; R.M. Yevych (Condensed Matter Physics, 2008)
Statistical theory for ferroelectrics based on triple well anharmonic potential was used for the case of structural second order phase transition in Sn2P2S6 crystals. Parameters of effective Hamiltonian of the model were estimated using available experimental data. These findings confirm the assumption that the phase transition in these crystals is located in crossover region between order-disorder and displacive type, and very closely to tricritical point.